The association between learning style, academic performance, and participation in co-curricular activities among second-year medical students in Universiti Putra Malaysia - Sa'at, Azmah; Mohd. Thani, Suryati; Abd. Manan, Nizar (A S E A N Journal of Teaching and Learning in Higher Education, 2024)
The extensive systemic module courses, defined by comprehensive study and frequent assessments, establish a demanding atmosphere for medical students. Students are required to balance their involvement in co-curricular activities. This study explores how learning preferences impact academic performance and participation in extracurricular activities among second-year medical students at Universiti Putra Malaysia. A cross-sectional study design was employed. The connection between the variables was determined through the application of Chi-Square and Fisher’s test. The Revised Two-Factor Study Process Questionnaire, comprising 20 questions, was utilised to analyse deep and surface learning approaches. To assess the level of student engagement in co-curricular activities, 9 questions from the College Learning Effectiveness Inventory and Involvement in College Activity Scale were incorporated. Assessment marks were assigned by the Faculty of Medicine and Health Sciences at Universiti Putra Malaysia to evaluate students' academic performance. Among the 87 respondents, 82.8% engaged in the co-curricular activity. A significant majority of respondents, 74.7%, indicated that the deep learning approach aids them in their studies. Regarding academic performance, 78.2% of students attained an average score. The results indicated that the learning style significantly influenced the academic performance of medical students, as demonstrated by a Fisher’s test yielding p = 0.042. The co-curricular activities of the pupils showed no significant effect on their academic performance, as indicated by a Fisher’s test value of p = 0.584. Students who often employed a superficial learning approach exhibited below-average academic performance. In contrast, students who employed deep learning approach exhibited enhanced academic outcomes.